Pengaruh Promosi, Produk dan Lokasi Terhadap Keputusan Menabung di BMT Usaha Dini (BUD) Boyolali - Giyanto, Giyanto; Prastiwi, Iin Emy; Romdhoni, Abdul Haris (ITB AAS INDONESIA Surakarta, 2024)
Baitul Maal Wat Tamwil (BMT) is generally oriented towards improving the welfare of members. Has carried out two activities, namely saving or entrusting and lending funds (money). With promotions and excellent service, people can find out what BMT is. The population determined by the author in this research is the residents of Boyolali Regency. Sampling in this research used a purposive sampling technique. The respondents selected by the author using this purposive sampling method were members of BMT Usaha Dini (BUD) Boyolali. Interviews in this research were conducted with BMT Usaha Dini Boyolali employees to find out the number of Wadiah savings customers, while interviews with customers aimed to find out the attractiveness of customers to become Wadiah savings customers at BMT Usaha Dini Boyolali. Meanwhile, this research observation was carried out by the researcher coming directly to the field. The data collection carried out in this questionnaire was done by distributing 50 questionnaires. The questionnaire will be divided into two parts. The first is related to customer characteristics based on demographic segmentation, such as name, gender, age, and address. The second part contains a statement, which is an explanation of the operational variables of service activities.